2021
DOI: 10.1088/1361-6528/abe785
|View full text |Cite
|
Sign up to set email alerts
|

A synergistic interplay between dopant ALD cycles and film thickness on the improvement of the ferroelectricity of uncapped Al:HfO2 nanofilms

Abstract: The Al:HfO2 ferroelectric nanofilms with different total thicknesses and distributions of Al-rich strips are prepared using atomic layer deposition (ALD) in an uncapped configuration. The synergistic interplay between the number of Al-rich layers and the thickness of total film offers the additional flexibility to boost the ferroelectricity of the resulting Al:HfO2 nanofilms. By carefully optimizing both the ALD cycles for dopant layer and the total film thickness in the preparation, the HfO2 nanofilms in post… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
12
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 31 publications
2
12
0
Order By: Relevance
“…Also, then the film was annealed in an oxygen atmosphere at 750 °C for 30 s to crystallize, as referred to in our previously reported work. 44 The as-grown CVD MoS 2 crystals were spin-coated with poly(methyl methacrylate) (PMMA, molecular weight: 495, Micro-Chem) for 500 ramps per minute (rmp)@10 s and 2000 rmp@50 s. After baking at 180 °C for 90 s, the Si/SiO 2 substrates were etched in 1 mol L −1 KOH solution. Then, the floating PMMA films were lifted off by using Si/Al:HfO 2 substrates.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, then the film was annealed in an oxygen atmosphere at 750 °C for 30 s to crystallize, as referred to in our previously reported work. 44 The as-grown CVD MoS 2 crystals were spin-coated with poly(methyl methacrylate) (PMMA, molecular weight: 495, Micro-Chem) for 500 ramps per minute (rmp)@10 s and 2000 rmp@50 s. After baking at 180 °C for 90 s, the Si/SiO 2 substrates were etched in 1 mol L −1 KOH solution. Then, the floating PMMA films were lifted off by using Si/Al:HfO 2 substrates.…”
Section: Methodsmentioning
confidence: 99%
“…The 10.2 nm thick Al:HfO 2 ferroelectric film with 7 mol % Al dopant concentration was directly deposited on heavily doped Si p-substrates by atomic layer deposition (ALD) at 280 °C/20 Pa using liquid tetrakis (diethylamide), hafnium (TDMAH), and trimethyl aluminum (TMA) as the Hf and Al precursors, and O 2 plasma as oxygen source. Also, then the film was annealed in an oxygen atmosphere at 750 °C for 30 s to crystallize, as referred to in our previously reported work . The as-grown CVD MoS 2 crystals were spin-coated with poly­(methyl methacrylate) (PMMA, molecular weight: 495, Micro-Chem) for 500 ramps per minute (rmp)@10 s and 2000 rmp@50 s. After baking at 180 °C for 90 s, the Si/SiO 2 substrates were etched in 1 mol L –1 KOH solution.…”
Section: Methodsmentioning
confidence: 99%
“…However, they require capping layer stress to stabilize the o-phase, which leads to high manufacturing cost and complicated processes . In Al-doped HfO 2 (HfAlO) thin films, the small atomic radius of Al exerts mechanical stress in HfO 2 unit cells, which stabilizes the o-phase. , Lee et al demonstrated that the ferroelectric phase of HfO 2 films was stabilized by doping aluminum, which has limited solubility, and the aluminum doping concentration significantly influenced the ferroelectricity of the HfO 2 thin films . Celano et al.…”
mentioning
confidence: 99%
“…10 In Al-doped HfO 2 (HfAlO) thin films, the small atomic radius of Al exerts mechanical stress in HfO 2 unit cells, which stabilizes the o-phase. 11,12 Lee et al demonstrated that the ferroelectric phase of HfO 2 films was stabilized by doping aluminum, which has limited solubility, and the aluminum doping concentration significantly influenced the ferroelectricity of the HfO 2 thin films. 13 Celano et al used the flexoelectric effect in HfAlO for inducing polar rotations in HfO 2 thin films by applying an external stress.…”
mentioning
confidence: 99%
“…Recently, the lamination of Al 2 O 3 films within a HfO 2 layer was found to be effective in obtaining ferroelectricity by local stresses among layers. 27) In addition, nanolamination of HfO 2 and ZrO 2 layers is reported to be effective in obtaining ferroelectricity by the unbalanced Hf-O and Zr-O bonding strength within the film. 28) As mono-or sub-mono layers can be achieved by the self-limiting deposition process in the atomic-layer deposition (ALD) tool, 29,30) the lamination process allows high flexibility for stabilizing the ferroelectric properties.…”
mentioning
confidence: 99%